Inflammation markers in atherosclerosis development - A. P. Shavrin; Ya. B. Khovaeva; V. A. Chereshnev; B. V. Golovskoy (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To study different inflammation markers at various stages of atherosclerosis progression.Material and methods. In 174 21-70-year-old people, brachial artery ultrasound (Aloka 5000) was performed to visualize atherosclerotic plaques and assess intima-media thickness (IMT). Immuno-enzyme analysis was used to measure plasma levels of C-reactive protein, CRP (SeroELISA test system, Diagnostic Systems Laboratories, USA), and cytokines — tumor necrosis factor alpha (THF-alpha), interleukins 1, 4 and 8 (IL-1, 2, and 8) (Russian test systems, Cytokine company, St. Petersburg).Results. The levels of CRP, IL-1, IL-8 and TNF-alpha were dependent on atherosclerotic process stage and IMT CRP levels typical for systemic inflammatory reaction were observed in individuals with subclinical atherosclerosis and patients with post-infarction cardiosclerosis.Conclusion. There was an association between IMT and latent inflammation activity. Qualitative changes in inflammation intensity were observed even at early stages of atherosclerosis development.